STUDING OF SUDDEN DEATHS IN MOSCOW - D. V. Elin (Бюллетень сибирской медицины, 2013)
In this retrospective study, we report the frequency and main causes of sudden deaths in Moscow over 3year period. Frequency of sudden death is 78 134 cases. Males were 63.0% of cases. The incidence of sudden death was highest in the 2 age extremes (39% were 40–59 year old and 57.5% were elderly). The most important direct causes of sudden death were cardiovascular diseases (93%). 15% of outpatient medical records were filled in the course of pronouncement of death. A divergence in diagnosis occurred in 45.1 % of cases.